Experimental Verification and Comparative Study of Various MPPT Algorithms. (1st January 2016) - Beck, Y.; Sober, N.
Abstract : Choosing and implementing a Maximum Power Point Tracking (MPPT) algorithm in a photovoltaic (PV) system, along with choosing the power converter, constitutes the fundamental basic capabilities of a photovoltaic system. MPPT techniques are implemented in photovoltaic systems to achieve full utilization of PV array output power. Today there is a wide variety of MPPT algorithms, each one has its advantages and disadvantages. This paper presents theoretical, as well as experimental comparison results, in several aspects regarding four MPPT methods based on the basic two MPPT algorithms (Perturb and Observe, Incremental Conductance), implemented on a single DC/DC converter, under the same experimental conditions. The theoretical and experimental comparison is performed for characteristics of ripple around the MPP and the convergence time. The experimental results are provided and supported by theoretical analysis and show that gradient based methods have better convergence time as well as ripple values in comparison to fixed step methods.